Foundations of clinical research applications to evidence-based practice - Portney, Leslie Gross (F.A. Davis, 2020)
The text of this fourth edition has maintained its dual perspectives. It is designed for those who do research to generate new knowledge and examine theories and for those who want to be critical consumers of evidence to inform clinical decision-making. All of us need to be able to critically evaluate research reports to inform practice and further study. The scope of the text allows it to fulfill different needs at different times. This edition will continue to serve this wide audience. It incorporates several important contemporary themes, including the application of evidence-based practice (EBP) for clinical decision-making, the imperative of interprofessional collaboration, the implications of translational research, and the focus of healthcare on quality of life, meaningful outcomes, and patient values. These directions and priorities continue to define research philosophies that guide the conduct of clinical inquiry, the types of questions that are deemed important, and how they influence advances in measurement and analysis techniques"--